2015
DOI: 10.1007/s00520-015-2726-5
|View full text |Cite
|
Sign up to set email alerts
|

Difficult choices for young patients with cancer: the supportive role of decisional counseling

Abstract: DeCo is useful to facilitate decision making and reduce decisional conflict. It plays a role in the perception of being informed while not directly providing clinical information. This model of decisional support intervention, in which information is provided only by the clinician and decisional support is focused on personal aspects that influence the decision, could improve shared decision making between patient and clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…The majority of patients demonstrated anxiety and clinically significant decisional conflict prior to their counselling sessions, as measured by the STAI and the DCS. These scores are not unexpected in this high‐risk prenatal population and are consistent with a study of cancer patients facing genetic testing and fertility options (Chiavari et al ). Anxiety and decisional conflict have been implicated as barriers to decision‐making (Ferron Parayre et al ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The majority of patients demonstrated anxiety and clinically significant decisional conflict prior to their counselling sessions, as measured by the STAI and the DCS. These scores are not unexpected in this high‐risk prenatal population and are consistent with a study of cancer patients facing genetic testing and fertility options (Chiavari et al ). Anxiety and decisional conflict have been implicated as barriers to decision‐making (Ferron Parayre et al ).…”
Section: Discussionsupporting
confidence: 89%
“…Patients have reported feelings of being taken more seriously by their physician, being given explanations that were easily comprehensible, and having greater involvement in decision‐making, while physicians have reported less unease and distress during interactions (Bieber et al ). Other benefits to patients include increased knowledge, perceived involvement, treatment uptake, satisfaction, psychological wellbeing, and global quality of life (Hack et al ; Hamann et al ; Loh et al ), as well as a reduction in decisional conflict (Bieber et al ; Chiavari et al ). SDM promotes ethical practice by supporting patients' autonomy, and a full understanding of medical options enables patients to assess their risks and benefits thus facilitating beneficence and minimizing non‐maleficence (Stiggelbout et al ).…”
Section: Introductionmentioning
confidence: 99%
“…La intervención propuesta en este estudio resulta novedosa en esta población, ya que si bien se han reportado intervenciones destinadas a ayudar en el proceso de toma de decisiones (Chiavari et al, 2015;de Geus et al, 2014;Listol et al, 2017) o al apoyo emocional, partiendo de un enfoque cognitivo conductual (Chiavari et al, 2015;Landau et al, 2015), poco se han utilizado las terapias llamadas de tercera generación (Broley, 2013) con pacientes con cáncer hereditario. En este sentido, se ha demostrado que estas terapias han resultado eficaces en población oncológica, utilizando técnicas de Mindfulness y la TAC (Butow et al, 2013;Lebel et al, 2014;Páez et al, 2007).…”
Section: Discussionunclassified
“…29 Chiavari et al reported that a decisional counseling session led to reduced decisional conflict about FP, whereas medical consultation, family support, and information gathered from the internet did not explain reductions in conflict. 30 Future research should determine the generalizability of these findings. Interventions may also be refined to address fertility issues among patients with different support needs and at different points in post-treatment survivorship.…”
Section: Post-treatment Decision Regret About Fertility Preservationmentioning
confidence: 93%